Application of Good Manufacturing Practices in Nutmeg Syrup Business in South Aceh Regency - Salman Farisi; Maya Indra Rasyid (Green Publisher Indonesia, 2022)
Nutmeg syrup is one of the processed nutmeg flesh products that has high selling potential, one of the producers of nutmeg syrup in the South Aceh area is Usaha Diyanti. The purpose of this research activity is to determine whether or not there is GMP application in the nutmeg syrup production process at Diyanti Enterprises, Hilir Village, Tapaktuan District, South Aceh Regency, Aceh Province through the Kedai Reka internship program, Merdeka Campus, Teuku Umar University 2021. This study uses a study method. field and interviews with Diyanti Business owners to find out the existing problems. The problem-solving method is done by making a questionnaire to the business owner. The application of Good Manufacturing Practices (GMP) aims to improve product quality and employee hygiene when processing products at home businesses and is safe for consumption by consumers. Aspects that are considered by consumers to be unfavorable really need to be observed and need to be improved, namely production room facilities, storage areas for finished products, employee hygiene in producing products in the home industry and aspects of product design and packaging to attract consumers' attention and want to consume beverage products nutmeg syrup.